3(-x-3)-4=4x-27

Simple and best practice solution for 3(-x-3)-4=4x-27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-x-3)-4=4x-27 equation:



3(-x-3)-4=4x-27
We move all terms to the left:
3(-x-3)-4-(4x-27)=0
We add all the numbers together, and all the variables
3(-1x-3)-(4x-27)-4=0
We multiply parentheses
-3x-(4x-27)-9-4=0
We get rid of parentheses
-3x-4x+27-9-4=0
We add all the numbers together, and all the variables
-7x+14=0
We move all terms containing x to the left, all other terms to the right
-7x=-14
x=-14/-7
x=+2

You can always share this solution

See similar equations:

| -5x+275-18x=2x+25 | | 5(2x+10=60 | | 13+5(x-1)=2(4x+2)+9 | | 49=7xx= | | 5+nn=13 | | 2x-122=0 | | 6n+18n=144 | | x/4+50=75 | | 7x^2-144/7=0 | | 4x+39+7x=116 | | 23x+2+2x+3=180 | | 1/3(6x-3)=-x+10+3x | | x/2+30=60 | | x/(x+1)=(x+6)/(x+1)-8/x | | 3x^2-42=105 | | 3u+7???u=0u=-74/5 | | 5x+2-6=-3x | | 9(2x-1)=7(2x | | 3(7+2m)=-15 | | 6x+16=20+180 | | 3(9+7x)=-57 | | 5x+2-6=3x | | 6x+16=20+188 | | 1x^2+5x-1=2 | | -1+7x=20 | | 2(6^2a+4)-8=48 | | 3x+6+2x+9=180 | | 2.3y=y-62 | | x=3+7/9 | | 8^b+2+4=63 | | 3x+62x+9=180 | | (y^2-y-2/5y)(10y/y+1)=2(y^2-y-2)/y+1 |

Equations solver categories